Mistakes at work are judged more negatively in routine tasks than in complex tasks - Tim Hampel (IU Internationale Hochschule, 2024)
Mistakes at work can lead to learning and personal development or can massively harm one's professional career. How a mistake affects a professional career often depends on how it is perceived by involved individuals (e.g. supervisors). In the present study we investigate two different types of mistakes at work: mistakes in routine and complex work tasks. In two experiments with 192 alumni of a German university we tested whether mistakes in routine tasks are judged differently than mistakes in complex work tasks. Results revealed that mistakes are judged significantly more negative when occurring in a routine work task compared to a complex work task. The results of our study give rise to a dilemma of mistakes at work where on basis of dual process theories mistakes are more likely to happen in routinized tasks while at the same time these mistakes are judged more negatively. We discuss an intervention to resolve the dilemma and suggest avenues for future research alongside the limitations of our study.
Keywords: M; 650; mistakes at work; errors; failures; attitudes towards mistakes; career development